Circularly polarized microstrip antenna array for the Ka-band - Varum, Tiago (2019)
The growing needs of higher transmission rates lead to the use of the Ka frequency bands and multi-beam technology, in the satellite communications, allowing more coverage. This fact leads to the need for the use of directive antennas and beamforming techniques to achieve a precise control of radiation pattern. This paper presents the design of a circularly polarized microstrip antenna array, at 29 GHz, suitable to satellite communications. The array will be a module part to develop an ample antenna array suitable to fulfill the satellite requirements, and feed with an electronic beamforming network.